"Monumentos de tinta e papel": cultura e politica na produção biografica da Coleção Brasiliana (1935-1940) - Thiago Lenine Tito Tolentino (2009)
This thesis is about the biographical brazilian production in the decades of 1930-1940. Through the biographies of Frei Caneca, Evaristo da Veiga, Paulo Eiró, Tavares Bastos, Silva Jardim, Farias Brito e Calógeras, they all published in the Coleção Brasiliana, the author intended to analyze the theoretical and historiographical points that guided the biographical writing at the time, as well as, highlight the contribution that the biographical work could give to the political-cultural interpretation about brazilian reality.